Application of Neural Network in Letter Recognition Using the Perceptron Method - Bagus Suteja (Bahasa Indonesia, 2022)
Modeling with neural networks is the learning and adjustment of an object. The perceptron method is a learning method with supervision in a neural network system. In designing a neural network that needs to be considered is the number of specifications that will be identified. A neural network consists of a number of neurons and a number of inputs. To identify some letters, it takes several neurons to distinguish them. These neurons will generate a combination value that is used to identify the letters. so that the resulting network must have parameters that can be set by changing through the rules of learning with supervision.